Pre-competitive anxiety and autonomic responses in professional U-20 futsal players: Effect of the competition phase and game location - Paludo, A. C.; Woodman, T.; Owen, J. A.; Rabelo, F. N.; Bernacikovà, M.; Simões, A. C. (Physiology & Behavior, 2022)
The study examined whether pre-competition anxiety and autonomic responses in elite futsal players change across the playoffs at away vs home venues. Heart rate variability, somatic and cognitive anxiety and self-confidence (by CSAI-2R questionnaire) were evaluated in nine male futsal players from a professional U-20 team, before competitive matches at the quarter-final, semi-final and final stages played at home and away venues. Two-way ANOVA for repeated measures was used, considering factor one the game location and factor two the playoff stage, with significance set at p<0.05. Significant effects of the playoff stage were demonstrated in the Mean of HR (F = 4.643; p = 0.014) and SD2 index (F = 14.83; p=<0.001)(quarter versus final). No difference was found for somatic and cognitive anxiety and self-confidence between the two factors. The results suggest that play at the final stage of the playoff, regardless of the game location, may cause higher physiological stress, demonstrated by elevated HR and decrease of SD2 index.